Kesembuhan Skin Flap H-Plasty dan Linear Closure untuk Penutupan Luka Area Lateral Thoraks - Erwin Erwin; Deni Noviana; Gunanti Gunanti; I Gusti Agung Ngurah Arphan Eka Putra (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Skin flap is one of the techniques use for large wound closure. This study were aimed to determine the rate of cure of skin flap H-plasty and linear closure based on subjective and objective clinical observation. Six male local cats at 1-2 years old, weighing 3-4 kg, were divided into two treatment groups. All cats were made 3 x 3 cm wound in the thoracic area for skin graft. Thoracic defects were treated with skin flap techniques H-plasty (group I) and linear closure (group II). Subjective observations was performed on days 3, 6, 9 and 12 after skin flap which was covering skin discoloration, pain response, time hair growth as well a bleeding tests that performed on the 18th day after the skin flap. Objective observation was made on day 18 by administration of 0.9% NaCland observed the absorption time, while the onset of drug effect was noticed by pupillary reflex observation after 0.2 ml adrenaline injection under the skin flap. The observation on day 9 showed that skin flap linear closure wasbetter than skin flap H-plasty, which was characterized by similar skin color with surrounding skin, reduced pain response and rapid hair growth. Bleeding blood test was showed a glowing red colored and immediately came outafter incision in both groups. The absorption time of 0.9% NaCl and the effects of adrenaline were faster in thegroup skin flap linear closure. Skin flap H-plasty and linear closure techniques can be applied to repair woundsin the thoracic area of cat skin, however, the linear closure flap of skin was healing faster than skin flap H-plasty.